Foreign Language Reading Anxiety of Indonesian EFL Senior High School Students - Irza Yuzulia (Darussalam English Journal (DEJ), 2025)
This research was conducted to investigate students’ reading anxiety in the EFL classroom in a Senior High School. The respondents of this study were 40 students of a Senior High School in Pekanbaru. This study used a qualitative descriptive method which investigated the levels of students’ anxiety and the causes of students’ anxiety in English reading class. The data were collected using the Foreign Language Reading Anxiety Scale (FLRAS), a set of questionnaires adopted from Ahmad et al. (2013), and interviews to clarify the responses from the questionnaires. The study revealed that most of the students perceived moderate to high levels of anxiety while reading English texts. It is found that the causes of students’ reading anxiety were mainly related to limited vocabulary knowledge, over-reliance on translation, difficulty in pronouncing words when reading aloud, and encountering unfamiliar or difficult topics. These findings indicate the importance of providing appropriate strategies and learning materials to reduce students’ anxiety and improve their reading comprehension in English.